Nomadic civilization of Central Asia - М, Хурметхан (Journal of International Studies, 2008)
The nomadic civilization has played an important role to the historical development of human life. As a fact of lifestyle, nomadism has distinguished from other civilizations with its overall characteristics and developed under the internal and external effects. In some historical periods, many people all around the world were living in the nomadic lifestyle. It was related to the certain factors such as an ecological condition of this region, tradition, materialistic, intellectual and cultural inheritance etc. In certain period of human development, the nomadic civilization was playing an important role to establish favorable environment to encourage relation between nature and society. This was belongs to the vast steppes of Central Asia, West Siberia, Arabic peninsula and Sahara. Even though, nomadic civilization has faced the danger of being disappeared time to time, there are nomads who are maintaining their nomadic lifestyle without any harm to the nature and eco-system, in globalized world. Studies on nomadism have a historical and cognitive importance which will be useful to develop theories and concepts for better and safer world. There are many scientific researches and studies on nomadic civilization which was made by scholars from many states. On the basis of these researches and studies, we can review a origin of nomadic civilization and its development periods, social and political structure, main characteristic of intellectual culture, domination and globalization, at the end its destiny.